Stokes 1.5 μm and anti-Stokes 0.99 μm emissions in Ga-Ge-Sb-S: Er3+ amorphous chalcogenide films prepared by pulsed laser deposition - Střižík, Lukáš; Oswald, Jiří; Vlček, Milan; Beneš, Ludvík; Pavlišta, Martin; Wágner, Tomáš (University of Pardubice, 2015)
Nowadays, rare-earth-doped materials play an important role in photonics. The reason can be seen in needs of present world for efficient data transfer, medical use, construction of modern devices and in research progress. We report the compositional dependence of Ga-Ge-Sb-S: Er3+ pulsed laser deposited (PLD) chalcogenide films allowing the efficient Er3+: 4I13/2 → 4I15/2 (λ ≈ 1.5 μm) Stokes and Er3+: 4I11/2 → 4I15/2 (λ ≈ 0.99 μm) anti-Stokes emissions at pumping wavelengths of 980 and 1 550 nm, respectively. It was found that the lowest antimony and the highest sulphur contents in Ga-Ge-Sb-S films doped with 0.5 at. % Er3+ are beneficial for both mentioned emissions. The photon up-conversion emission was confidently observed in the case of PLD film with the highest content of sulphur, i.e., (Ge17.8Ga3.6Sb3.6S75)99.5Er0.5. The shape of this emission band is comparable with the photon up-conversion emission observed in the bulk sample. We have also inspected the dependence of target material composition on deposition rate of the PLD. The substitution of the antimony atoms with the gallium atoms leads to lower deposition rate.